Антология выдающихся достижений в науке и технике. Часть 31: Портрет харьковского физика Александра Ильича Ахиезера - Баранов, М.И. (Електротехніка і електромеханіка, 2016)
Приведен краткий научно-исторический очерк об известном физике-теоретике Харьковщины − академике АН УССР
(НАН Украины) Ахиезере А.И. и его выдающемся вкладе в мировую физическую науку Наведено короткий науково-історичний нарис про відомого фізика-теоретика Харківщини − академіка АН УРСР
(НАН України) Ахієзера О.І. і його видатний внесок в світову фізичну науку Purpose. Description is in the short form of the basic distinguished scientific achievements, features of personality and way
of life of the known Kharkov physicist-theorist A.I. Akhiezer.
Methodology. Existent scientific approaches for treatment and
systematization of physical knowledges. Methods of historical
method at research of development in human society of basic
sections of theoretical physics. Results. Short information is resulted about the basic creative and vital stages, and also fundamental scientific achievements of the indicated prominent physicist of the XX century. Some personal qualities of this Kharkov
physicist-theorist, becoming a founder known in the world of
physical school are described. Originality. First the Kharkov
scientist-electro-physicist for the wide circle of readers imagined
a short scientifically-historical essay the known physicist of contemporaneity, being based on his scientific labours and published
materials about him. Practical value. Scientific popularization of
creative activity of the known Kharkov physicist and his achievements in area of theoretical physics. Next reminder a wide reader
on the example of creative life in science and got prominent scientific results of labour of one human personality known in the scientific world about incessant in modern society connection of
times and generations.